Self-serving counterproductive work behaviors: The development and validation of a scale - Fariha Zahid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
Within the body of knowledge in counterproductive work behaviors (CWB), a large majority of researchers categorizes these behaviors under the common rubrics of theft, aggression, violence, sabotage, alcohol use, substance abuse, and absenteeism. However, researchers indicate that the current inventories of counterproductive work behaviors are not applicable to all contexts, situations, and jobs. The current study aims to extend the scope of available inventories of CWB by developing and validating a scale for self-serving counterproductive work behaviors by following scale development guidelines by Hinkin (1998) in two independent studies. An EFA, and CFA performed in study 1 revealed that the finally retained eight items showed an alpha reliability coefficient of 0.83, whereas the CFA results confirmed for the convergent and discriminant validities. Moreover, the replication of the scale psychometrics in study 2 corroborated the convergent and discriminant validity of the developed scale with an internal consistency value of 0.79. This study contributes in the growing body of literature in CWB domain as the first study to develop a scale for the measurement of self-serving CWB as a distinct category of negative behaviors and holds significant implications for theory and practice. The study further discusses theoretical implications, limitations, and directions for future research.
Keywords: 330; counterproductive work behaviors; scale development; self-serving behaviors; machiavellianism; political nature